Yandex Users' Needs in Knowledge on Psychology - Juliet A. Kitova; Natalia R. Aprelikova (Peoples' Friendship University of Russia (RUDN University), 2019)
Modern information technology space provides people with new opportunities for learning about the world, acquiring additional knowledge and satisfying cognitive needs. The paper analyzes the requests and characteristic features of the needs for knowledge on psychology of the Internet users in the Russian Federation. The study was conducted on the basis of the search queries in Yandex. The speciﬁc user requests demonstrate a heterogeneous level of interest in various branches of psychology, which allows highlighting the structural and substantial features of the respondents' needs in psychology knowledge and the forms of obtaining the kind of knowledge they prefer. In general, the research results showed a high level of interest of the Internet users in knowledge on psychology, demonstrated their high orientation towards the search for useful information on personal development, professional activities and the development of favorable relationships with others. The data obtained indicate the most important areas of knowledge on psychology for a modern person and will be useful in the framework of psychological and educational theory and practice. The article points out that the study of the needs of the population in knowledge on psychology should be an integral part of the psychological community, which is responsible for the psychological well-being of people and the development of the psychological culture of society as a whole.